Do poder mágico da formação às práticas de formação com projecto e à avaliação reflexiva - Manuel António Silva F. (Universidade do Minho, 2000)
Our central goal is to question the «intrinsic goodness of training activities» by analysing the dominant ways of conceiving and exercising teachers training, and identifying its virtues and limitations from a theoretical point of view that assumes the concepts of emancipation and domination as central axes. Training practices aim to provide the teachers with means to construct their profession in a autonomous and responsible way or, on the contrary, assume an «instrumental and adaptative rationality» (Dubar, 1991), resulting in conformist attitudes and maintenance of the «reproduction cycle» (or domination cycle)? Our final goal is to explore how a «democratic evaluation» (MacDonald, 1987) of training could contribute to analysing processes of conceiving and practising training, therefore rehabilitating the concept and demystifying some of the dominant practices in the field.